Navigating the Nuances of Contemporary Narratives: A Critical Exploration of Modern Trends in the Urdu Novel - Dr. Zahid Akhtar Shaheen,; Dr. Shazia Andleeb (Corresponding Author),; Rubina Tufail,; Nasreen Akhtar,; Sidrah Rahman,; Shaukat Hussain, (Al-Qanṭara, 2023)
Embarking on a journey through the transformative landscape of Urdu novels unveils a tapestry richly woven with the threads of socio-political and cultural narratives of the South Asian subcontinent. The evolution of Urdu novels is not merely a literary progression but a reflection of the societal, political, and cultural metamorphosis that has shaped the region. From tales that were deeply rooted in love and social norms, Urdu novels have burgeoned into a robust genre exploring a plethora of themes that mirror the multifaceted issues and ideologies of contemporary society.The historical trajectory of Urdu novels, particularly during the British colonial era, provides a lens through which the societal struggles, aspirations, and the stark dichotomy between various social classes during that period can be examined. The narratives, often poignant and reflective, served not only as a commentary on the prevailing conditions but also as a critique of the socio-political structures and norms that governed society.In the contemporary context, Urdu novels have embraced diverse themes, such as gender dynamics, social justice, and post-colonial identities, reflecting the complexities and challenges that pervade modern society. Writers like Umera Ahmed and Mohsin Hamid have navigated through themes of love, existential struggles, globalism, and existential anxiety, exploring the internal and external worlds of characters that resonate with readers across the globe.This article seeks to dissect the evolution and contemporary trends within Urdu novels, providing a meticulous overview of its historical context, thematic progression, influential writers, and its pervasive impact on society and culture. Through a detailed exploration of these facets, the article aims to offer insights into the past, present, and potential future of Urdu novels within the literary domain of South Asian literature.